Prolonged Impella 5.0/5.5 support within different pathways of care for cardiogenic shock: the experience of a referral center - Pieri, Marina; Ortalda, Alessandro; Altizio, Savino; Bertoglio, Luca; Nardelli, Pasquale; Fominskiy, Evgeny; Lapenna, Elisabetta; Ajello, Silvia; Scandroglio, Anna Mara (Frontiers in Cardiovascular Medicine, 2024)
Impella 5.0 and 5.5 are promising low invasive left ventricle (LV) temporary mechanical circulatory supports (tMCS) for cardiogenic shock due to mechanical LV unloading paired with powerful hemodynamic support. The aim of this study was analyse data and destinies of patients supported with Impella 5.0/5.5 at a national referral center for cardiogenic shock and to assess parameters associated with myocardial recovery and successful weaning.Single-center observational study of all patients treated with Impella 5.0 or Impella 5.5 from March 2018 to July 2023.Fifty-nine patients underwent Impella 5.0/5.5 implantation due to profound cardiogenic shock: acute myocardial infarction was the most frequent cause of shock (42 patients, 71%). Median duration of Impella support was 13 days (maximum duration 52 days). Axillary cannulation was feasible in almost all and 36% were mobilized during support. Forty-four patients (75%) survived to next therapy/recovery: 21 patients experienced recovery, 15 were bridged to long term LVAD and 8 to heart transplantation. Global survival was 66%. Predictors of native heart recovery at multivariate analysis were the number of days on tMCS before upgrade to Impella 5.0/5.5 (hazard ratio 0.68 (0.51-9) p=0.0068) and improvement of LV EF within the first 7-10 days of support (hazard ratio 4.72 (1.34-16.7) ,p=0.016).Transcatheter systems as Impella 5.0/5.5 revolutioned the field of tMCS. Myocardial recovery is the primary clinical target: its prognostication and promotion are key to ensure the most proficuous course to each patient from cardiogenic shock to long-term event-free survival.